A Novel CD48-Based Analysis of Sepsis-Induced Mouse Myeloid-Derived Suppressor Cell Compartments. (26th February 2017) - Jia, Bei; Zhao, Chenchen; Li, Guoli; Kong, Yaxian; Ma, Yaluan; Wang, Qiuping; Wang, Beibei; Zeng, Hui
Abstract : Myeloid-derived suppressor cells (MDSCs) are a heterogeneous subset of cells that expands dramatically in many disease states and can suppress T-cell responses. MDSCs mainly include monocytic and granulocytic subpopulations that can be distinguished in mice by the expression of Ly6G and Ly6C cell surface markers. This identification system has been validated in experimental tumor models, but not in models of inflammation-associated conditions such as sepsis. We challenged growth factor independent 1 transcription repressor green fluorescent protein (Gfi1:GFP) knock-in reporter mice with cecal ligation and puncture surgery and found that CD11b + L y 6 G l o w L y 6 C h i g h MDSCs in this sepsis model comprised both monocytic and granulocytic MDSCs. The evidence that conventional Ly6G/Ly6C marker analysis may not be suited to study of inflammation-induced MDSCs led to the development of a novel strategy of distinguishing granulocytic MDSCs from monocytic MDSCs in septic mice by expression of CD48. Application of this novel model should help achieve a more accurate understanding of the inflammation-induced MDSC activity.